DIFFERENCE IN THE GPS DEFORMATION PATTERN OF NORTH AND CENTRAL ZAGROS (IRAN) - Walpersdorf A.; Hatzfeld D.; Vernant P.; Chéry J.; Masson F.; Nankali H.; Tavakoli F.; Nilforoushan F.; Tatar M. (My University, 2006)
Measurements on either side of the Kazerun fault system in the Zagros Mountain Belt, Iran, show that the accommodation of the convergence of the Arabian and Eurasian Plates differs across the region. In northwest Zagros, the deformation is partitioned as 3-6 mm yr-1 of shortening perpendicular to the axis of the mountain belt, and 4-6 mm yr-1 of dextral strike-slip motion on northwest-southeast trending faults. No individual strike-slip fault seems to slip at a rate higher than ~2 mm yr-1. In southeast Zagros, the deformation is pure shortening of 8 ± 2 mm yr-1 occurring perpendicular to the simple folded belt and restricted to the Persian Gulf shore. The fact that most of the deformation is located in front of the simple folded belt, close to the Persian Gulf, while seismicity is more widely spread across the mountain belt, confirms the decoupling of the surface sedimentary layers from the seismogenic basement. A comparison with the folding and topography corroborates a southwestward propagation of the surface deformation. The difference in deformation between the two regions suggests that right-lateral shear cumulates on the north-south trending Kazerun strike-slip fault system to 6 ± 2 mm yr-1. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CONTINENTAL DEFORMATION; FAULT MOTION; GLOBAL POSITIONING SYSTEM (GPS); PLATE CONVERGENCE; SATELLITE GEODESY; ZAGROS